Aktivitas Antiadhesi Kombinasi Ekstrak Daun Pepaya dan Daun Sirih Hijau Terhadap Neutrofil pada Streptococcus Mutans, Staphylococcus Aurues dan Escheriachia Coli - Nining Kurniati (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2023)
Indonesia, according to the 2018 Riskesdas National Survey, as many as 45.3% or 1.2 million people experience dental caries. Antibiotics are used to treat these infections. Antibiotics are substances produced by a microorganism, which have the ability to inhibit the growth or kill microorganisms. In developing countries there is a problem, the emergence of strains of bacteria resistant to antibiotics in infectious diseases. The papain contained in papaya leaves is a proteolytic enzyme that also has a bactericidal and bacteriostatic effect, it is expected that the combination of betel leaves strengthens the activity of inhibiting the growth of Gram positive and negative bacteria. Research method laboratory experimental design, completely randomized design. An anti-adhesion activity test was carried out by adding a combination of papaya leaf extract and green betel leaf 5%, 15% and 25% on neutrophil isolates exposed to Streptococcus mutans, Staphylococcus aureus, Escherichia coli compared to controls. The ability of anti-adhesion activity was observed to decrease the adhesion of bacteria to neutrophil cells, tested by Anova and Benferroni. Antiadhesion test of 15% and 5% extracts with statistical tests decreased adhesion to Streptococcus mutans on neutrophils (Sig 0.00), did not decrease adhesion to Staphylococcus aureus and Escherichia coli (Sig 1.00).